Equivalent of Locality of Ground Waters in Mirzachul - Korakhonova, Yulduz; Namozov, Khushvakt (International Journal of Psychosocial Rehabilitation, 2020)
In this article observed profundity assay of contemporary agro-chemical and ameliorative stipulation of most important irrigated soils spreading in the area of, to determine the variability of productivity in the soil and to elaborate on scientific base for its enhancement. It serves as a basis for soil-moistening consider of soil agrophysics properties, soil moisture content, soil salinity and irrigation norms, irrigation procedures and land reclamation arrangements with the scientific basis for effective land use. This problem solves the geomorphological, lithological and hydrogeological conditions of soils, and their genesis and accumulation of salts in the soil layers is scientifically justified. Under the influence of anthropogenic factors, the process of evolutionary transformation of soils cover on irrigated soils, identification of the degree of fertility of irrigated soils and drawing up maps of soil quality, as well as the development of a lodge of measures to maintain and increase fertility. Inception of productivity models for irrigated soils using technologies of the geoformation scheme and maturation of solutions aimed at upkeep and enhancement of soil fertility.